Smart and Functional Soft Materials - Dong, Xufeng (IntechOpen, 2019)
During the past 100 years, a large number of new materials have been developed, which provide us with various tools, wares, clothes, etc. with good properties but low weight and low cost. Recently, smart soft materials that can respond to an external stimulus (such as an electric field, magnetic field, sound, light, temperature, pH, and so on) as well as functional soft materials that are electronically, magnetically, or thermally conductive have attracted considerable attention. They have application potentials in various fields. To some extent, they are the way to fulfill most of the "black technology" described in the world of science fiction. This book introduces several smart soft materials and functional soft materials, which are of interest to scholars in related fields.